The Nature of Exchange Rate Movements and Exchange Rate Exposure: The Bangladesh Case. (August 2019) - Choi, Sunghee; Salam, Md. Abdus; Lee, Ki-Dong
This article analyses whether the effect of exchange rate changes on firms' returns, known as the 'exchange rate exposure' of firms, varies with the nature of exchange rate movements. Using Bangladesh as a case study, we identify multiple structural breakpoints in a Bangladesh exchange rate time series from January 1999 to June 2013, which allows us to divide the whole period into multiple sub-periods. By estimating the exchange rate exposure of non-financial Bangladeshi firms for each sub-period, we find that most firms are significantly exposed in the sub-period spanning May 2011 to June 2013, when movements in the exchange rate between the Bangladeshi taka and the US dollar are unprecedentedly turbulent. This finding is consistent when trade-weighted exchange rates are used. Our results suggest that corporate investors and policymakers in Bangladesh need to be aware of firms' exchange rate risk when the taka–dollar exchange rate, as the primary indicator, moves significantly away from the previous patterns.